Do transfer payments affect food loss in rural household? Empirical evidence from China - Li, Xiaoxiao; Li, Yujiao; Hu, Nanyan; Luo, Yi; Wu, Laping (Frontiers in Sustainable Food Systems, 2025)
IntroductionIn 2024, China issued the “Action Plan for Grain Conservation and Anti-Food Waste,” signifying a new phase in the efforts towards food security and waste reduction. Reducing food loss at the farm level is a crucial component of this action plan. This paper studies the impact of transfer payments on food loss in rural households.MethodsUsing data from a field survey on 1,196 rural households across six provinces of China, this study build Tobit models to conduct the empirical test.ResultsThe results show that: (1) The relationship between transfer payments and household food loss exhibits an inverted U-shape, whereby the loss rate first increases and then declines with rising levels of transfer payments. This non-linear effect remains robust across various model specifications and sample robustness checks. (2) Heterogeneity analysis indicates that the impact of transfer payments is significantly stronger among small-scale farmers, households located in western regions, and those with limited farming experience. (3) In addition, natural disasters, food quality, and the gender of the household decision-maker are found to exert statistically significant effects on food loss.DiscussionThis study presents a better understanding of the actual impacts of transfer payments on food loss in rural China, and provides valuable insights for other countries or regions that also engage in the improvement of income to reduce food loss and waste.